Pelvimetria em macacos-da-noite (Aotus azarai infulatus - KUHL, 1820) - Do Valle, Cristiane Macedo del Rio; Do Valle, Rodrigo del Rio; Monteiro, Frederico Ozanan de Barros [UNESP]; de Castro, Paulo Henrique Gomes; Valentim, Renato; Carvalho, Reinaldo de Amorim; Muniz, José Augusto Pereira Carneiro; Bombonato, Pedro Primo (My University, 2006)
Related data to the diameters of the pelvis from 72 Aotus azarai infulatus, owl monkeys, 42 adult males and 30 adult non-pregnant females, were obtained in vivo by ventrodorsal projection radiographic exams, correlated with sex, the measures of the body and their origin. The mean values of the body length (30.94 cm), tail length (35.63 cm), thoracic perimeter (18.97 cm), hip perimeter (17.11 cm) and the weight (0.96 Kg) were verified. The radiographic images were digitalized and measured, and the mean values were 1.41 cm for the superior biiliac diameter; 1.58 cm for the inferior biiliac diameter; 1.97 cm for the medium biiliac diameter; 2.64 cm for the right diagonal diameter; 2.66 cm for the left diagonal diameter; 2.48 cm for the sacrum-pubic diameter; 3.85 cm 2 for the inlet pelvic area. In conclusion, the pelvis from males and females Aotus azarai infulatus can be classified as dolicopelvic and there is pelvic sexual dimorphism in adult owl monkeys (Aotus azarai infulatus).
Pelvimetry on owl monkeys (Aotus azarai infulatus - KUHL, 1820)
Keywords: Macacos; Monkeys; Pelve; Pelvis; Primatas; Primates; Aotus (primate); Aotus azarai; Aotus trivirgatus